Stimuli-response of MOFs in Drug Delivery Systems - Yin Hang (MATEC Web of Conferences, 2024)
Metal-organic frameworks (MOFs) attracted much attention of researchers in biomedicine because of its diverse functions, tuneable pore sizes, and large surface area. MOFs act as a possible drug delivery system and have numerous advantages. It exhibits high loading of drug, biocompatibility, target delivery of drugs, cytotoxicity, and biodegradability. The sizes of MOFs can also be changed without changing its topology. It makes MOFs a appropriate drug delivery carrier in various situations. In recent years, MOFs have become a multifunctional drug carrier, and researchers have designed a variety of MOFs based drug delivery strategies. The significant efficacy of these strategies is also verified. Therefore, exploring MOFs in drug delivery systems is of vital importance. This work mainly discusses about the formulation of drug-delivery MOFs and different kinds of stimuli-response of MOFs. Along with them, the efficacy of the MOFs drug delivery system are also demonstrated experimentally. It is acknowledged that using MOFs to delivery drug is a new method of curing and have a better treatment than current. This work can do help to the further research on the stimuli-response of MOF drug delivery systems.